Anomalous width variation for rarefactive ion acoustic solitary waves in the presence of warm multi-ions - Ghosh, S.S.; Sekar Iyengar, A.N. (My University, 2002)
A previous analysis of anomalous width variation for a single-ion rarefactive solitary wave [S. S. Ghosh and A. N. Sekar Iyengar, Phys. Plasmas, 4, 3204 (1997)] has been extended to a multi-ion species, and shows that the corresponding width-amplitude characteristics depend crucially on the respective ion concentrations; for example, with increasing light-ion concentration, an 'increasing-width' rarefactive solitary wave transforms to a 'deereasing-width' one for a constant Mach number exhibiting an overall U-shaped variation profile. The influence of the second ion species generally decreases with increasing amplitude, being maximum for the single to multi-ion transition. However, in the neighbourhood of double-layer-like solutions, the influence again becomes prominent, which may be associated with the corresponding energy-amplitude relations for both the ions.
Keywords: Theoretical study; Onecomponent plasma; Rarefaction wave; Solitary wave; Plasma ion acoustic waves; Anomalous width variation